2018
DOI: 10.1099/mic.0.000665
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Helicobacter pylori NY43 strain and its prophage-cured derivatives

Abstract: This study aimed to determine the characteristics of the Helicobacter pylori host NY43 strain and its prophage-cured derivative. H. pylori colonizing the human stomach cause many diseases. They show high genetic diversity, allowing the development of mutant strains that can form bacterial communities adapted to specific environmental conditions. Bacteriophage activities are associated with bacterial evolution, including pathogenicity development. Herein, we reported the complete genome sequence and genomic org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A recent study indicated that the presence of bacteriophages induces genetic alterations in the host genome, leading to the continuous production of prophage-free derivatives that coexist in H. pylori microbial communities (Vale et al, 2008) and confer diversity in morphology, motility, viability, and pathogenicity. Further, this study reported that KHP30 prophage could specifically suppress CagA expression (Takeuchi et al, 2018). Another study conducted using an H. pylori strain isolated from an ethnic minority patient in China revealed the presence of a 32.5 kb prophage integrated into the genome and demonstrated that most of its genes (30/33) were the same as those of KHP30; however, in this case, the prophage was inserted between two putative virulence genes, oipA and homB, which encode adherence factors that mediate interactions between H. pylori and the host microenvironment.…”
Section: H Pylori Prophagesmentioning
confidence: 67%
See 1 more Smart Citation
“…A recent study indicated that the presence of bacteriophages induces genetic alterations in the host genome, leading to the continuous production of prophage-free derivatives that coexist in H. pylori microbial communities (Vale et al, 2008) and confer diversity in morphology, motility, viability, and pathogenicity. Further, this study reported that KHP30 prophage could specifically suppress CagA expression (Takeuchi et al, 2018). Another study conducted using an H. pylori strain isolated from an ethnic minority patient in China revealed the presence of a 32.5 kb prophage integrated into the genome and demonstrated that most of its genes (30/33) were the same as those of KHP30; however, in this case, the prophage was inserted between two putative virulence genes, oipA and homB, which encode adherence factors that mediate interactions between H. pylori and the host microenvironment.…”
Section: H Pylori Prophagesmentioning
confidence: 67%
“…Available information on H. pylori prophage diversity indicates that prophages and bacteria share a complex evolutionary history (Vale et al, 2017) and that the bacterial genome has been widely modified, in diverse regions, via horizontal gene transfer (Takeuchi et al, 2018). A few studies have investigated the presence of phages in other H. pylori strains; for example, a study from 2016 reported the detection of a 31.7 kb prophage in an H. pylori strain isolated from a Mexican patient with gastric cancer (Mucito-Varela et al, 2016).…”
Section: H Pylori Prophagesmentioning
confidence: 99%
“…Bioinformatics prediction and analysis were performed using the published complete genome sequence of H. pylori phage KHP30 (NC_019928.1) and 1961P (NC_019512.1) (Lehours et al 2011 ; Luo et al 2012 ; Uchiyama et al 2012 , 2013 ; Abdel-Haliem and Askora 2013 ; Takeuchi et al 2018 ). Preliminary annotations and reports of H. pylori phage endolysin and holin were used in combination with the NCBI BLAST program (e-values ≤ 0.01 were considered credible); the smallest item in the credible range was subjected to the next round of BLAST.…”
Section: Methodsmentioning
confidence: 99%
“…A Japanese group studied behaviours of a KHP30-infected strain of H. pylori and novel phage-free derivative strains. Their motility assays showed that the motility of the prophage-free derivatives was considerably decreased compared with that of the parent strain, but the phage-free derivatives showed higher growth rates than the parent KHP30-infected strain [ 103 ]. Moreover, they found both parent and derivative strains had alternation in a major virulence gene sequence, which was 22-bp (5′-tcaatgttggaaaaaattccga-3′) insertion at nucleotide position 2471 in the cagA gene, resulting in the disruption of the open reading frame of cagA due to a frame-shift mutation.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Moreover, they found both parent and derivative strains had alternation in a major virulence gene sequence, which was 22-bp (5′-tcaatgttggaaaaaattccga-3′) insertion at nucleotide position 2471 in the cagA gene, resulting in the disruption of the open reading frame of cagA due to a frame-shift mutation. As a result, CagA expression was not detected by Western blot in any of these strains, suggesting the prophage infection attenuates the pathogenicity by altering the sequence of cagA and the flanking sequences upstream of the cagA gene [ 103 ]. Certainly, the insertion of temperate phages into the bacterial chromosome can disrupt expression of bacterial genes or their regulatory regions, although phages may be able to restore the disrupted bacterial gene (or regulatory region) by providing a viral copy of that gene [ 104 ].…”
Section: Gastric Cancermentioning
confidence: 99%